Heading up to the Hearst estate office, and to Miss Morgan's office [job responsibilities], October 17, 1927 (1927)
List of assigned responsibilities for three managers associated with the Hearst property at San Simeon during construction. 'Heading up to' likely refers to whom each manager reports.